THE RIGHT OF ACCESS TO INFORMATION: an analysis from the Spanish and Brazilian realities - Gardini Santos, Joao Carlos [UNESP]; Fernandez Molina, Juan Carlos; Chaves Guimaraes, Jose Augusto [UNESP] (Univ Federal Campina Grande, 2017)
The issue of information access has significantly affected Information Science, nowadays, especially in archives, as a way of guaranteeing citizenship. In the case of Brazil and Spain, there are, in both legal systems, laws that guarantee the right of access to public information, although there are divergences regarding its legal nature. In this way, the objective was to identify and analyze comparatively how information access is treated in the current Spanish and Brazilian legislative and doctrinal contexts. To do so, we started with a literature review followed by the identification and application of the following subject categories: object, scope, publicity, definitions, limits, procedure, resources, responsibilities, supervision and taxation, based on the methodology of Bardin's content analysis. The results revealed that the Brazilian's legislation is more specific and detailed than the Spanish's in conceptual issues (definition, object and procedures) while the question of limits is broader in Spain, referring to the protection of the State and with reference to the environment. This concern is more formal in Spain, with the establishment of the Consejo de Transparencia y Buen Gobierno, while in Brazil there is the Controladoria Geral da Uniao, at federal level, in addition to the generic reference to the supervisory and monitoring authority.
Keywords: Law of Access to Information; Administrative transparency; Information organization; Content analysis